Midwife conceptualizations of clinical leadership in the labor ward of district hospitals in KwaZulu-Natal, South Africa - Mianda S; Voce AS (Dove Medical Press, 2018)
Solange Mianda, Anna S Voce Discipline of Public Health Medicine, School of Nursing and Public Health, College of Health Sciences, University of KwaZulu-Natal, Durban, South Africa Background: In South Africa, inadequately skilled health care providers and poor clinical leadership are continually linked to preventable perinatal and maternal mortality, which calls for improved clinical skills among health care providers and for strong clinical leadership at the bedside. Very little has been done to ensure clinical leadership at the bedside in the labor ward of district hospitals. One strategy implemented has been the appointment of District Clinical Specialist Teams, introduced to improve the quality of maternal and child health care in district hospitals and clinics through the provision of clinical leadership as an outreach activity. However, the strengthening of clinical leadership at the bedside remains neglected. Further, clinical leadership in the literature is not conceptualized in the same way across settings.Aim: To explore midwife conceptualizations of clinical leadership in the labor ward of district hospitals in KwaZulu-Natal.Methods: Iterative data collection and analysis, following the Corbin and Strauss grounded theory approach, was implemented. In-depth interviews were carried out with the midwifery members of the District Clinical Specialist Teams in KwaZulu-Natal. The emergent theoretical framing of clinical leadership was presented and discussed at a workshop with broader midwifery representation, leading to a final proposition of the conceptualization of clinical leadership among midwives.Results: The emergent conceptualization of clinical leadership comprised five major dimensions: the definition of clinical leadership, the context in which clinical leadership takes place, the conditions related to clinical leadership, the actions and interactions involved in clinical leadership, and the effects of clinical leadership.Conclusion: Clinical leadership is an emergent phenomenon arising from dynamic interactions in the labor ward and the broader health system, which converge to attain optimal patient care. Clinical leadership is not being understood from a traditional hierarchical perspective, as vested only in a positional leader. Keywords: bedside care, clinical leadership, frontline health workers, midwives, grounded theory, leadership, qualitative research, patient outcomes